Cross-Cultural Adaptation of the Developmental Coordination Disorder Questionnaire in Turkish Children - ACAR, GÖNÜL (SAGE PUBLICATIONS INC, 2019)
The Developmental Coordination Disorder Questionnaire (DCDQ'07) is an instrument for screening children between 5 and 15 years of age. Although it is popular, this instrument has not been adapted for use with Turkish children, and there is no valid similar screening tool in Turkey. Thus, this study aimed to provide a cross-cultural adaptation of the DCDQ'07 for Turkish children. We performed the translation process using well-established cross-cultural adaptation guidelines, and we recruited 736 parents (361 males, 375 females) of typically developing children with a mean (M) age of 9.27 years (standard deviation = 2 years 5 months, range: 5.0-14.9 years). We determined the internal consistency of the questionnaire by item and total score correlations, Cronbach's alpha and item-deleted Cronbach's alpha. Intraclass correlation coefficients were used to determine test-retest reliability after an interval of 5 days. The Cronbach's alpha of the Turkish DCDQ'07 was .890 for the total questionnaire. All the item-deleted Cronbach's alpha values were lower than the total value of .890, except the bull in a China shop item (Cronbach's alpha values .896). Test-retest reliability ranged from .99 to 1.00. The Turkish DCDQ is a valid and reliable screening tool for assessing the motor performance of children between 5 and 15 years of age.
Keywords: developmental coordination disorder; questionnaire; cross-cultural adaptation; diagnosis; clumsy; DCDQ; RELIABILITY; VALIDITY; VERSION